2021
DOI: 10.1001/jamaneurol.2021.3356
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Methylphenidate on Apathy in Patients With Alzheimer Disease

Abstract: OBJECTIVETo measure whether methylphenidate compared with placebo decreases the severity of apathy in individuals with Alzheimer disease. DESIGN, SETTING, AND PARTICIPANTSThis multicenter randomized placebo-controlled clinical trial was conducted from August 2016 to July 2020 in 9 US clinics and 1 Canadian clinic specializing in dementia care. A total of 307 potential participants were screened. Of those, 52 did not pass screening and 55 were not eligible. Participants with Alzheimer disease, mild to moderate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 41 publications
1
66
0
1
Order By: Relevance
“…Based on clinical anecdotal reports, MPH is being considered for the treatment of apathy in AD, and preliminary trials have shown promising outcomes (Padala et al, 2018;Mintzer et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Based on clinical anecdotal reports, MPH is being considered for the treatment of apathy in AD, and preliminary trials have shown promising outcomes (Padala et al, 2018;Mintzer et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Methylphenidate, a noradrenaline-dopamine reuptake inhibitor, has recently been found to have efficacy in treatment of apathy in Alzheimer’s dementia. 52 Further understanding of the effects of dopaminergic medication regime on apathy and anhedonia in PD is needed, in addition to RCTs of dopaminergic agents for apathy and anhedonia across different disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Drugs known to increase alertness, such as modafinil, amphetamine and cocaine, act by inhibiting reuptake, as do antidepressants such as reboxetine, venlafaxine and duloxetine 67 . Methylphenidate, the mainstay of ADHD treatment, acts by inhibiting both NE and dopamine reuptake in the PFC to improve attention and memory 125 and has been suggested as a potential treatment for attentional impairment and apathy in AD 60 , with a recent placebo‐controlled study showing that it does reduce the latter 126 …”
Section: Promising Noradrenergic Therapiesmentioning
confidence: 99%
“…67 Methylphenidate, the mainstay of ADHD treatment, acts by inhibiting both NE and dopamine reuptake in the PFC to improve attention and memory 125 and has been suggested as a potential treatment for attentional impairment and apathy in AD 60 , with a recent placebo-controlled study showing that it does reduce the latter. 126 Atomoxetine is by far the most extensively studied drug of this class. As well as its established benefits in ADHD, atomoxetine has been shown to boost executive function in PD and is both safe and tolerable.…”
Section: Norepinephrine Reuptake Inhibitorsmentioning
confidence: 99%